2007
DOI: 10.2105/ajph.2006.103788
|View full text |Cite
|
Sign up to set email alerts
|

Use of Tobacco Cessation Treatments Among Young Adult Smokers: 2005 National Health Interview Survey

Abstract: Evidence-based tobacco cessation treatments are underused by young adult smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
116
2
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(127 citation statements)
references
References 15 publications
5
116
2
4
Order By: Relevance
“…7 Government programs for tobacco control have helped curtail the smoking epidemic in Brazil and elsewhere in the world. 8 In Brazil, the group that most often seeks help at smoking cessation support groups in public health units are women with a mean age of 50 years and low educational attainment. 9 Perhaps, this group represents a population that does not work and thus has a more flexible schedule to attend weekly therapy sessions at health units.…”
Section: Discussionmentioning
confidence: 99%
“…7 Government programs for tobacco control have helped curtail the smoking epidemic in Brazil and elsewhere in the world. 8 In Brazil, the group that most often seeks help at smoking cessation support groups in public health units are women with a mean age of 50 years and low educational attainment. 9 Perhaps, this group represents a population that does not work and thus has a more flexible schedule to attend weekly therapy sessions at health units.…”
Section: Discussionmentioning
confidence: 99%
“…The concurrent use of these tobacco products may increase adolescents' risk for developing nicotine dependence (Jordan & Delnevo, 2010;Knishkowy & Amitai, 2005), thus making it difficult to quit smoking and achieve long-term abstinence (Curry, Sporer, Pugach, Campbell, & Emery, 2007). A growing body of literature has examined the development and progression of nicotine dependence among adolescent cigarette smokers (DiFranza et al, 2007;O'Loughlin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…An estimated 70% of the 45 million adult smokers in the United States see a health care provider each year, representing over 31 million opportunities for brief intervention and treatment (25). A Cochrane Collaboration meta-analysis of randomized trials concluded that brief advice to quit from a health care provider significantly increases cessation rates (59).…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of data from the 2000 National Health Interview Survey found that the relationship between receipt of advice to quit by a health care provider and use of cessa-TFCPS: Task Force on Community Preventive Services tion aids was strongest among Medicaid recipients and the uninsured, compared with smokers with private health insurance (17). A separate analysis of the 2005 National Health Interview Survey found that use of pharmacotherapy more than doubled among young adult smokers (aged 18 to 24 years) who received advice to quit smoking from a health care provider (25).…”
Section: Introductionmentioning
confidence: 99%